Дольник у румунській та українській авангардистський поезії - Paladian, Kristiniia (Чернівецький національний університет, 2015)
The article deals with the study of dolnik structure in Romanian and Ukrainian avant-garde poetry. It is shown that the national forms of avant-garde dolnik were formed on the base of sharp opposition to classical norms of versification. The ways of creation and a rhythmic base of background forms of dolnik were found: Romanian – difficult, not regular that mainly belongs to polymorphic structure at the level of micropolymetria or is directed on the naked tonic; Ukrainian – acts as a polymorphemic structure, where two lines are emphasized: the interaction with classical sizes and an exit into naked tonic.
Dolnik in Romanian and Ukrainian avant-garde poetry
Keywords: avant-garde; versification; classical versification; tonic versification; dolnik